(untitled) (Annals of Medical Research, 2021)
Aim: The electrocardiographic QT dispersion (QTd), Tpe/QT ratio and Tpeak-Tend (Tpe) interval have been known as ventricular repolarization indices. Neutrophil–to- lymphocyte ratio (NLR) is an inflammatory marker that is newly described. Increased QTd, Tpe/QT ratio, inflammation and Tpe interval are associated with ventricular arrhythmia (VA). In patients with severe aortic stenosis (AS), VA has a key role in terms of morbidity and mortality. The present study aimed at examining whether transcatheter aortic valve implantation (TAVI) affects ventricular repolarization indices and NLR. Material and Methods: Study population consisted of a total of 44 patients undergoing TAVI. Echocardiographic and laboratory parameters of patients were evaluated before TAVI and sixth month after TAVI. Comparioson of electrocardiographic QTd, Tpe/QT ratio, Tpe interval and NLR of the same petients were made before TAVI and sixth month after TAVI.Results: QT interval, corrected QT interval and heart rate were similar before and after TAVI (p>0.05 for all). There was a statistically significant decrease in QTd (26.0±9.1 vs. 21.3±7.2 ms; p=0.008), Tpe interval (88.43±12.6vs. 78.8±10.1 ms; p0.001), NLR (3.08±2.0 vs. 2.16±0.73; p=0.001) and Tpe/QT ratio ( 0.23±0.3 vs. 0.21±0.1; p=0.024) after TAVI. Morever, the reduction in the Tpe interval and Tpe / QT ratio after TAVI was found to be significantly correlated with NLR (r=0.400, p=0.007; r=0.396, p=0.008; respectively).Conclusion: TAVI does not only reduce symptoms in patients with severe AS, but may also be effective in reducing risk of VA by improving factors affecting ventricular repolarization.